DETERMINANTS OF HEALTH WORKERS' DIGITAL COMPETENCE FOR EMR IMPLEMENTATION - Siswanto, Siswanto; Syah, Tantri Yanuar Rahmat; Hamdi, Edi; Dewi, Sandra (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to regularly identify and synthesize the key factors influencing digital competence among health workers in the implementation of Electronic Medical systems. Using the PRISMA-guided Systematic Literature Review (SLR) method, 84 documents from Scopus and PubMed were initially retrieved and screened, yielding 8 peer-reviewed articles published between 2020 and 2025 that met the inclusion criteria. The findings reveal that digital competence is shaped by five interconnected factors: individual readiness, education system design, institutional policies, continuous digital training, and validated assessment tools. Furthermore, digital competence moderates the effectiveness of emerging technologies such as AI and supports holistic care delivery. The novelty of this study lies in its integrative mapping of empirical and conceptual evidence to address existing research gaps. This review offers theoretical insight and practical implications for educators, healthcare managers, and policymakers committed to advancing digital transformation in health systems.